2019
DOI: 10.3390/ijerph16214262
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Respiratory Health Outcomes and Coal Mine Fire PM2.5 Smoke Exposure: A Cross-Sectional Study

Abstract: In 2014, wildfires ignited a fire in the Morwell open cut coal mine, Australia, which burned for six weeks. This study examined associations between self-reported respiratory outcomes in adults and mine fire-related PM2.5 smoke exposure. Self-reported data were collected as part of the Hazelwood Health Study Adult Survey. Eligible participants were adult residents of Morwell. Mine fire-related PM2.5 concentrations were provided by the Commonwealth Scientific and Industrial Research Organisation Oceans & Atmosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
0
30
1
Order By: Relevance
“…The study has several strengths. Unlike observational studies that have used only secondary data (such as hospitalization) to assess respiratory health, this research has built upon previously collected hospitalisation[10] and self-reported symptom data[12] with the inclusion of objective measures of lung mechanics. A further strength of this study was the inclusion of individual estimates of PM 2.5 exposure utilising a combination of detailed time-location diaries and spatially and temporally resolved modelling of PM 2.5 concentrations based upon coal combustion and weather conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study has several strengths. Unlike observational studies that have used only secondary data (such as hospitalization) to assess respiratory health, this research has built upon previously collected hospitalisation[10] and self-reported symptom data[12] with the inclusion of objective measures of lung mechanics. A further strength of this study was the inclusion of individual estimates of PM 2.5 exposure utilising a combination of detailed time-location diaries and spatially and temporally resolved modelling of PM 2.5 concentrations based upon coal combustion and weather conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective modelling of the spatial and temporal distribution of mine fire-related PM 2.5 concentrations by the Australian Commonwealth Scientific and Industrial Research Organisation (CSIRO) Oceans & Atmosphere[19,20] was used due to the absence of ground-level air pollution monitoring at the beginning of the mine fire. Individual level mean daily PM 2.5 exposures over the mine fire period (51 days, between 9 February to 31 March, 2014) were estimated through linking time-location diary data (reported in the Adult Survey) with the modelled fire-related PM 2.5 exposure data as described by Johnson et al[12]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent study reported increased asthma related ED visits and hospital admissions during PM2.5 elevations caused by a six-week long coal mine fire in Australia [15]. Other studies by that group documented increased symptoms, outpatient visits, and medication use for respiratory disease, including asthma, during this same OAP incident [16,17]. Increased respiratory symptoms were reported by nearby residents during and for several weeks after a large industrial fire in Texas, US, which burned and released PM2.5 and black carbon into the atmosphere for several days [18].…”
Section: Literature Reviewmentioning
confidence: 93%
“…The HHS Hazelinks Stream which utilises administrative health datasets, has previously reported more COPD related emergency department presentations [16], medications dispensed for respiratory conditions [17] as well as visits to specialist respiratory services [18] during the mine fire period. The HHS Adult Survey, carried out 2.5 years after the mine fire, also identified higher risks of self-reported respiratory symptoms associated with individual-level mine fire PM 2.5 exposure [19]. The aim of this analysis was to evaluate clinical respiratory outcomes more than 3.5 years after the fire, particularly the risk of COPD and related respiratory symptoms, and their association with individual-level coalmine fire PM 2.5 exposure.…”
Section: Introductionmentioning
confidence: 99%